2020
DOI: 10.1101/2020.09.17.20196709
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of vital signs on the death of patients with new coronavirus pneumonia: A systematic review and meta-analysis

Abstract: Background: Assessing the impact of vital signs (blood pressure, body temperature, heart rate, respiratory rate, and oxygen saturation) on the death of patients with new coronavirus pneumonia would provide a simple and convenient method for the monitoring of subsequent illness, and therefore, in some degree reduce treatment costs and increase the cure rate clinically. Methods: Six databases were retrieved. The software R 3.6.2 was used for meta-analysis of the included literature. Results: 12 studies were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…The emergence of symptoms was noticed in an escalating manner in the group of mild and moderate symptoms, pneumonia, severe and critical to the group of non‐survivors. The major clinical features noted were fever and cough, consistent with other SRs 47,48 . Besides, we detected that dyspnea, chest pain and anorexia were relatively ominous clinical signs for the seriousness of the disease and mortality.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The emergence of symptoms was noticed in an escalating manner in the group of mild and moderate symptoms, pneumonia, severe and critical to the group of non‐survivors. The major clinical features noted were fever and cough, consistent with other SRs 47,48 . Besides, we detected that dyspnea, chest pain and anorexia were relatively ominous clinical signs for the seriousness of the disease and mortality.…”
Section: Discussionsupporting
confidence: 77%
“…However, heterogeneity was still high for non‐specified reasons. Most of the previous SRs reported the same heterogeneity even with including only adults into their analysis system 47 . It indicated that the Covid‐19 behaviour pattern was so hard to be predicted.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Important changes related to vital signs have been documented during the admission of patients infected with COVID-19, such as an increase in baseline temperature as well as heart and respiratory rates. This assessment is indispensable, since reduced SPO 2 and increased blood pressure, heart rate, and respiratory rate are independent risk factors for mortality in patients with COVID -19, with emphasis on SPO 2 and high blood pressure [ 36 , 37 ]. A study published in The Journal of the American Medical Association (JAMA) revealed that at the time of screening, 30.7% of patients were febrile and 17.3% tachypneic [ 13 ].…”
Section: Discussionmentioning
confidence: 99%